A MOF‐Based Spatial‐Separation Layer to Enable a Uniform Favorable Microenvironment for Electrochemical CO2 Reduction - Xu Han; Ting Zhang; Martí Biset-Peiró; Siqi Zhao; Sebastian Murcia Lopez; Kim Daasbjerg; Joan Ramon Morante; Jian Li; Jordi Arbiol (Small Structures, 2023)
Regulating the local microenvironment of active sites to increase their specific CO2 concentration and pH gradient, is a promising approach to optimize the electrochemical CO2 reduction reaction (eCO2RR). However, currently reported morphological strategies display an uncertainty to the compatibility and distribution between catalytic sites and their microenvironment. Here, a uniform spatial‐separation metal–organic framework (MOF) layer between active sites and bulk electrolyte is proposed, which enables each active site to locate in a similarly favorable microenvironment. Zinc oxide (ZnO) nanorods (NR), a representative electrocatalyst for eCO2RR, is covered with a Zeolitic imidazolate framework‐8 (ZIF‐8) thin layer to serve as a model system. The prepared ZnO NR@ZIF‐8 exhibits an enhanced Faradaic efficiency toward CO at a wide range of potentials and reaches a maximum FE of CO (85%) at −1.05 V versus reversible hydrogen electrode, which is one of the best records till date. Moreover, the hydrophobic ZIF‐8 layer protects ZnO against self‐reduction. Such performance benefits from the porous ZIF‐8 shell with high CO2 affinity, realizing efficient CO2 access and retaining an increased local pH near ZnO active sites.